DESIGN AND DEVELOPMENT OF A PROTOTYPE FOR A WEB-BASED INTERFACE FOR ONLINE MATERIAL FOR TANZANIAN YOUTH - Chumo, C.; Mjema, E. A.M. (Tanzania Journal of Engineering and Technology, 2018)
A prototype of a web-based interface for an online database was developed to be used by youth organizations in Dar-es-Salaam. A participatory approach involving secondary students in the identification of user interface requirements, in designing and testing the prototype was used. A questionnaire was designed and manned in seven secondary schools in Dar-es-Salaam to estimate the Internet usage. Interviews were conducted to countercheck the questionnaire responses. The interview and the questionnaire helped to come up with a set of user requirements for the web-based interface of an online information search. From the specifications of the user requirements the author was able to create a youth-friendly web based prototype that can be used by youth groups in Dar-es-Salaam.